Welded connections at high‐strength steel hollow section joints. (16th May 2022) - Stroetmann, Richard; Kästner, Thoralf; Rust, Brian; Schmidt, Jan
Abstract: The calculation of the loadbearing capacity of hollow section joints using the design formulas according to EN 1993‐1‐8 assumes full‐strength welded connections if the non‐linear stress distribution over the circumference is not covered by calculation. Sufficient ductility in the connections ensures a plastic redistribution capacity within each joint. In the case of hollow section structures made of high‐strength steels, it becomes more difficult to meet the requirement for full‐strength welds as the yield strength of the base material increases. This article begins with a summary of the current rules for the design and execution of welded hollow section joints. The softening behaviour of high‐strength steels and the loadbearing capacity of welded connections with local softening in the HAZ are then discussed. That is followed by the presentation of the results from the AiF‐FOSTA research project P1020 regarding the influence of manufacturing parameters on the properties of welded connections and the HAZ. The experimental test programme for single‐sided welded T‐connections and the parameter studies within the research project P1453 are also described. Finally, a design approach is presented to account for HAZ failure and hybrid failure modes of hollow section connections.